Pattern Place - Mputa, Thozama (School of Architecture, Planning and Geomatics, 2018)
Cape Town's solitary ﬁred power station was commissioned in 1961 and opened in 1962 and demolished on the 22 February 2010. A landmark to the city that was not protected under the Heritage Act as it was 48 years old. The power station is the last coalfired power station still standing in Cape Town. The site is well located between movement routes and local communities, large buildings and structures are present on site. The site offers an exciting redevelopment opportunity that can result in a variety of land uses for local and visitors, residential commercial, retail and community facilities. Although site is well located within movement routes these are boundaries, which are barriers between three distinct yet historical neighbourhoods Athlone, Pinelands and Lange. The design will use pattern from site to break down the barriers, promote connectivity through access and movement routes and create place for economic activity, recreational activity and housing.